Surface Plasmon Resonance as a Characterization Tool for Lipid Nanoparticles Used in Drug Delivery - Chain, Cecilia Yamil; Daza Millone, María Antonieta; Cisneros, José Sebastián; Ramirez, Eduardo Alejandro; Vela, María Elena (Frontiers in Chemistry, 2021)
The development of drug carriers based in lipid nanoparticles (LNPs) aims towards the synthesis of non-toxic multifunctional nanovehicles that can bypass the immune system and allow specific site targeting, controlled release and complete degradation of the carrier components. Among label free techniques, Surface Plasmon Resonance (SPR) biosensing is a versatile tool to study LNPs in the field of nanotherapeutics research. SPR, widely used for the analysis of molecular interactions, is based on the immobilization of one of the interacting partners to the sensor surface, which can be easily achieved in the case of LNPs by hydrophobic attachment onto commercial lipid- capture sensor chips. In the last years SPR technology has emerged as an interesting strategy for studying molecular aspects of drug delivery efficacy such as LNPs´ interactions with biological targets, serum proteins and tumor extracellular matrix. Moreover, SPR has contributed to the obtention and characterization of LNPs, gathering information about the interplay between components of the formulations, their response to organic molecules and more recently, the quantification and molecular characterization of exosomes. By the combination of available sensor platforms, assay quickness and straight forward platform adaptation for new carrier systems, SPR is becoming a high throughput technique for LNPs´ characterization and analysis.